2018
DOI: 10.1038/s41598-018-21889-7
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis in an in vitro Fibroblast Model of Idiopathic Pulmonary Fibrosis Reveals Potential Role for CXCL14/CXCR4

Abstract: Idiopathic Pulmonary Fibrosis (IPF) is a progressive disorder that is marked by an over accumulation of activated fibroblast populations. Despite the improved understanding of many mechanisms within this disease, global gene expression analysis has few focused studies on the fibroblast, the central effector cell of progressive fibrosis. We present a unique analysis of IPF pulmonary fibroblasts as they transition through cell culture and identify in vitro altered cellular processes. Fibroblasts were isolated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…We speculate that a recapitulation of this morphology may promote degenerative human NP cells to assume a more juvenile phenotype. Our data suggests that VP treatment is able to support morphological changes, which shows association with a transition in degenerative NP cells to decrease expression of the fibroblastic markers CTGF, ACTA2, S100A4, and DDR2 87‐98 . and increase expression of known markers of NP and notochordal phenotype KRT19, LAMA1, and KLF6, NOG, and THBS2 14,19,60‐62 .…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…We speculate that a recapitulation of this morphology may promote degenerative human NP cells to assume a more juvenile phenotype. Our data suggests that VP treatment is able to support morphological changes, which shows association with a transition in degenerative NP cells to decrease expression of the fibroblastic markers CTGF, ACTA2, S100A4, and DDR2 87‐98 . and increase expression of known markers of NP and notochordal phenotype KRT19, LAMA1, and KLF6, NOG, and THBS2 14,19,60‐62 .…”
Section: Discussionmentioning
confidence: 64%
“…Our data suggests that VP treatment is able to support morphological changes, which shows association with a transition in degenerative NP cells to decrease expression of the fibroblastic markers CTGF, ACTA2, S100A4, and DDR2. [87][88][89][90][91][92][93][94][95][96][97][98] and increase expression of known markers of NP and notochordal phenotype KRT19, LAMA1, and KLF6, NOG, and THBS2. 14,19,[60][61][62] It should be noted, though, that these VP-induced effects may be unable to completely shift cells toward profiles consistent with juvenile NP, as previously specified markers, such as CDH2 and BASP1, were downregulated at all three time points.…”
Section: Upregulated Gene Setsmentioning
confidence: 99%
“…Our data have now shown that C2 cells can induce the expression of ACTA2 in PF and that this effect is likely to be mediated by means of miR‐27a downregulation. It is known that normal fibroblasts can adapt to in vitro culture systems by promoting markers typically associated with fibroblast activation such as ACTA2 [46], which could explain the weak positive signal for ACTA2 in our control groups. Nevertheless, our results showed a marked increase in ACTA2 fluorescent signals and mRNA upregulation in coculture and transfection experiments.…”
Section: Discussionmentioning
confidence: 88%
“…The gathered data showed that poly P suppresses intestinal inflammation and fibrosis through downregulating of the expression of inflammation- and fibrosis-associated molecules in the intestinal epithelium [ 44 , 92 ]. Furthermore, it had been published that the CXCL14/CXCR4 chemokine axis is involved in the progression and/or activation of fibroblasts during initiation of pulmonary fibrosis in the lung [ 93 ]. In tunr, one therapeutic starting treatment could be the application of 2-aminopurine [ 94 ].…”
Section: Discussionmentioning
confidence: 99%